Separation of hemopoietic cells from adult mouse marrow by use of monoclonal antibodies. - Hoang, T; Gilmore, D; Metcalf, D; Cobbold, S; Watt, S; Clark, M; Furth, M; Waldmann, H (1983)
Primitive hemopoietic progenitor cells from adult mouse marrow have been substantially enriched by virtue of a negative selection procedure with monoclonal antibodies. It has been possible to segregate erythroid progenitor cells at distinct stages of differentiation on the basis of their cell surface antigens. This has been achieved with two monoclonal antibodies reactive with the mature elements of bone marrow. YBM 34.3 binds to a heat-stable antigen expressed on B lymphocytes, neutrophils, and cells of the erythroid lineage. YBM 6.1 reacts with cells of the neutrophil, eosinophil, and monocyte series but does not bind to colony-forming cells. Separation is achieved by indirect immunoadsorption (panning) with YBM 34.3 on Protein-A-coated plastic plates followed by FACS II cell sorting with YBM 6.1. The combined procedures yield a marrow population containing 58% immature cells (blasts, promyelocytes, and myelocytes) and 9.5% clonogenic cells. In addition, differential binding of YBM 34.3 can be used to segregate erythroid progenitor cells at distinct stages of differentiation (day 7 BFU-E, day 5 BFU-E and CFU-E) either by cell sorting or panning. It is shown that both techniques give a comparable degree of resolution of the different cell types with, however, an appreciable advantage of panning over cell sorting in allowing the rapid handling of large numbers of cells.